On the legitimacy of coercion for the nancing of public goods - Felix Bierbrauer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
The literature on public goods has shown that e?cient outcomes are impossible if participation constraints have to be respected. This paper addresses the question whether they should be imposed. It asks under what conditions e?ciency considerations justify that individuals are forced to pay for public goods that they do not value. It is shown that participation constraints are desirable if public goods are provided by a malevolent Leviathan. By contrast, with a Pigouvian planner, e?ciency can be achieved. Finally, the paper studies the delegation of public goods provision to a pro?t-maximizing ?rm. This also makes participation constraints desirable.
urn:nbn:de:bvb:19-epub-13287-3
Keywords: D02; D82; H41; L51; 330; Public goods; Mechanism Design; Incomplete Contracts; Regulation